Streptolysin S induces proinflammatory cytokine expression in calcium ion-influx-dependent manner - Yugo Yamamori; Rina Shirai; Kazuto Ohkura; Hideaki Nagamune; Toshifumi Tomoyasu; Atsushi Tabata (Current Research in Microbial Sciences)
Anginosus group streptococci (AGS) are opportunistic pathogens that reside in the human oral cavity. The β-hemolytic strains of Streptococcus anginosus subsp. anginosus (SAA) produce streptolysin S (SLS), a streptococcal peptide hemolysin. In recent clinical scenarios, AGS, including this species, have frequently been isolated from infections and disorders beyond those in the oral cavity. Consequently, investigating this situation will reveal the potential pathogenicity of AGS to ectopic infections in humans. However, the precise mechanism underlying the cellular response induced by secreted SLS and its relevance to the pathogenicity of AGS strains remain largely unknown. This study aims to elucidate the mechanism underlying the host cellular response of the human acute monocytic leukemia cell line THP-1 to secreted SLS. In THP-1 cells incubated with the culture supernatant of β-hemolytic SAA containing SLS as the sole cytotoxic factor, increased Ca2+ influx and elevated expression of proinflammatory cytokines were observed. Significantly reduced expression of SLS-dependent upregulated cytokine genes under Ca2+-chelating conditions suggests that Ca2+ influx triggers SLS-dependent cellular responses. Furthermore, SLS-dependent enhanced expression of IL-8 was also implicated in the activation of extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (MAPK) signaling pathways. The findings presented in this study are crucial for a comprehensive understanding of the real pathogenicity of SLS-producing β-hemolytic AGS in the latest clinical situations.